DESKRIPSI GANGGUAN KEPRIBADIAN PADA ANAK DIDIK LEMBAGA PEMASYARAKATAN ANAK KELAS II A KUTOARJO - Retno Ristiasih Utami; Agung Santoso Pribadi (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2013)
The purpose of this study is to describe personality disorders of prisoners from Kutoarjo Children Penitentiary. The descriptive method is used to analyze data that conducted with Millon’s Adolescent Clinical Inventory (MACI). Population of this research is 117 prisoners from Kutoarjo Children Penitentiary, the subjects were determined through an incidental sampling technique (n = 59), 13 – 20 years, male and female. Result reveal based on average score of 30 indicators of MACI that types of clinical personality are negativistic, depressive and histrionic. The problems that occurred are family discord, social insensitivity and peer insecurity. Clinical syndromes are delinquent predisposition, impulsive propensity, substance abuse proneness and depressive affect